Investigating the Impact of Venture Capital on te Success of Construction Sector SMEs in the UK - Sarraf, Ali (Digital Repository of Theses - SSBM Geneva, 2025)
SMEs operating in the construction sector in the UK are beneficial owing to their significant contribution to the country’s GDP, employment rates, and economic growth. However, most of them face substantial financing-related challenges, with most new SMEs closing down because of inadequate capital. Venture capital offers a unique solution to these SMEs’ challenges; however, its impact on the UK construction sector remains unknown. The purpose of this sequential exploratory mixed-methods case study was to explore the opinions of financial experts in the construction sector regarding how VC impacts the success and growth of SMEs operating in their industry in the UK. The target population in the research were financial experts in SMEs in the UK construction sector with at least five years of experience. The participants were sampled purposively (qualitative part) using simple random sampling (quantitative), and their responses were analysed thematically using Pearson correlation and regression analysis, respectively. Ethical considerations, including using informed consent forms and maintaining participant anonymity, were also upheld. Findings revealed that venture capitalists enhance the financial and non-financial performance metrics of the construction sector SMEs in the UK, including their investment returns, sales revenue, profit margins, quality, safety, competitiveness, technological innovativeness, employee satisfaction, productivity, turnover, inventories and overall sustainability. The results also indicated the essence of the skills and experience of their management team, milestones, and market validation in venture capital investment decisions. SME owners were identified as Future research might be conducted using other types of experts or similar professionals in SMEs in other industries in the UK or different countries.